Effect of heating and stretching membrane on ionic conductivity of sulfonated poly(phenylene oxide) - Li, C.; Liu, J.; Guan, R.; Zhang, P.; Zhang, Q.
With chlorosulfonic acid as sulfonating agent, sulfonated poly(phenylene oxide)(SPPO)was prepared by homogeneous method and SPPO membranes were cast from its solutions in dimethylacetamide. The obtained membrane of SPPO was heat-treated and stretched with different forces by thermal mechanical analyzer under its glass transition temperature. In addition, the effects of stretching and heating on ion conductivity of SPPO were investigated by using Solatron phase analyzer. It was shown that the mechanical stretching of SPPO has great effect on electric properties of SPPO under proper heating treatment, and the highest conductivities achieved were increased about 10 times that of the original membranes and reached 0.0983 S cm-1. The X-ray diffraction indicated that the molecular chains of SPPO were arranged more regularly under constraint during the heat treatment, and the scanning electron microscopy demonstrated that the morphologies of the film surfaces possessed more co-continuous regions and the hydrophilic ionic sulfonic acid groups orientated at stretching direction and connected more regularly, which facilitated the exchange and transfer of hydrated proton among these hydrophilic sulfonic acid groups.
Keywords: SULFONATION; POLY(PHENYLENE OXIDE); CONDUCTIVITY; STRETCH; PEM